Potential of oil palm (elaeisguineensis) empty fruit bunch fibres cement composites for building applications (2019)
This study was designed to evaluate the physical and mechanical properties of cementbonded composite made from oil palm (Elaeisguineensis) empty fruit bunch (OPEFB) fibres. The production variables investigated were pre-treatment of fibres with water at varying temperatures (cold, 60°C and 100°C), five chemical additive (NaOH) concentrations (2%, 4%, 6%, 8%, and 10%), OPEFB fibres ash content at three cement replacement levels (10%, 20%, and 30%) and three fibre contents (5%, 10%, and 15%) by weight of cement. The composites were tested for modulus of elasticity (MOE), modulus of rupture (MOR), internal bonding strength (IBS), compressive strength, density, thickness swelling (TS),and water absorption (WA). The pre-treatment of fibre with water at a temperature of 60°C and a NaOH concentration of 8% significantly enhanced and modified the performance of the composites. It increased MOE (from 5.5 to 8.9GPa) and MOR (from 3.6 to 7.3MPa), and decreased WA (from 26.2 to 12.8%) and TS (from 2.5 to 0.5%). The results revealed that pre-treatment of fibres, partially replacing cement with OPEFB fibre ash and fibre contents had a marked influence on the properties of the composite board produced (p< 0.05). It was concluded that pre-treatment of OPEFB fibres, when optimised, enhanced the sorption resistance and some mechanical properties of the cement composite.